Age‐related patterns of antler development in free‐ranging white‐tailed deer. Issue 6 (15th July 2014) - Hewitt, David G.; Hellickson, Mickey W.; Lewis, John S.; Wester, David B.; Bryant, Fred C.
ABSTRACT The relationship of antler size at one age to that at a later age is important in cervid management, in part by defining the effects of selective harvest based on antler characteristics. We used capture and harvest records from 2, 948 male white‐tailed deer (Odocoileus virginianus) on 5 study sites over a 10‐year period to define age‐antler size relationships. Antler size (Boone and Crockett score converted to cm) increased with deer age to 5 years of age, and we therefore considered males mature at ≥5 years of age. Antler size at ≥2 years of age was positively related to yearling antler size with antler size increasing 0.64 cm (SE = 0.07) for every cm of yearling antler score. Antler size at maturity increased 0.52–0.78 cm (SE = 0.05–0.12) for each cm of antler size at 2, 3, and 4 years of age. Number of yearling antler points is a criterion in some selective harvest regimes. Yearling deer with ≤3 antler points had antlers at maturity that were 32 cm (SE = 8.4 cm) smaller than deer with ≥4 antler points as yearlings. Because of a relationship between yearling antler size and antler size at later ages, selective harvest at young ages can influence antler size of deer remaining in the cohort at later ages. © 2014 The Wildlife Society.